BUDAYA HUKUM PENGRAJIN PERAK TERHADAP PENDAFTARAN HAK CIPTA SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 28 TAHUN 2014 (Studi Kasus: Pada Pengrajin Perak di Kabupaten Gianyar) - Ni Ketut Suniasih; I Gusti Ngurah Anom (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2021)
This study aims to determine the legal culture of the silversmiths of copyright registration which plays a role in providing legal protection for works of creation and can improve the creator's economy. The location of this research covers the Gianyar Regency area, to be precise, it focuses more on Sukawati and Ubud Districts as well as in the Office of the Ministry of Law and Human Rights of Bali Province.Based on the results of the study, it was found that: 1) The legal culture of silver craftsmen in Gianyar Regency is related to the enactment of Law Number 28 of 2014 concerning copyright, namely a culture that emphasizes the principles of mutual cooperation and togetherness, even tends to be communal. 2) There are two factors that affect copyright registration, namely external factors from the government in charge of providing socialization about copyright, internal factors that hinder copyright registration, namely the public mindset that considers copyright registration not urgent, internal factors that encourage knowledge of copyright. rewards and royalties that can be obtained after registering copyright.